The linearization of the relationship between scene luminance and digital camera output levels - Czech, Eugeniusz; Czyżewski, Dariusz (Photonics Letters of Poland, 2021)
This paper presents the results of linearity testing of the integrated image sensor of a CCD-equipped digital camera. The study demonstrated the lack of linearity of the characteristics of the sensor when scaling with the luminance standard signal. In the course of the research the function approximated by the fifth-degree polynomial was determined. After the appropriate transformation, this function would enable the linearization of the signal from the studied image sensor. The study demonstrated the possibility of linearizing the signal of integrated image sensors for correct luminance measurements. Thus, the possibility of reducing the nonlinearity error of integrated image sensors was discussed. Full Text: PDF References T. Tashiro, S. Kawanobe, T. Kimura-Minoda, S. Kohko, T. Ishikawa, and M. Ayama, "Discomfort glare for white LED light sources with different spatial arrangements," Lighting Research and Technology, vol. 47, no. 3, pp. 316-337, 2015, doi: 10.1177/1477153514532122. CrossRef A. de Vries, J. L. Souman, B. de Ruyter, I. Heynderickx, and Y. A. W. de Kort, "Lighting up the office: The effect of wall luminance on room appraisal, office workers' performance, and subjective alertness," Building and Environment, 2018, doi: 10.1016/j.buildenv.2018.06.046. CrossRef E. Czech and I. Fryc, "Illumination quality measurement of the work-station," in Proc. SPIE 5566. Optical Security and Safety, 2004, vol. 5566, pp. 239-242. CrossRef D. Czyzewski, "Monitoring of the lighting conditions of a street illuminated with road lights equipped with LEDs," Przeglad Elektrotechniczny, vol. 86, no. 10, pp. 170-172, 2010. DirectLink S. Słomiński, "Identifying problems with luminaire luminance measurements for discomfort glare analysis," Lighting Research and Technology, vol. 48, no. 5, pp. 573-588, 2016 CrossRef D. Czyzewski, "Monitoring of the subsequent LED lighting installation in Warsaw in the years 2014-2015," in Proceedings of 2016 IEEE Lighting Conference of the Visegrad Countries, Lumen V4 2016, 2016, pp. 1-4, CrossRef F. Greffier, V. Muzet, V. Boucher, F. Fournela, and R. Dronneau, "Use of an imaging luminance measuring device to evaluate road lighting performance at different angles of observation," in Proceedings of the 29th Quadrennial Session of the CIE, 2019, pp. 553-562. CrossRef D. Czyżewski, "Comparison of luminance distribution on the lighting surface of power LEDs," Photonics Letters of Poland, vol. 11, no. 4, pp. 118-120, 2019, doi: 10.4302/plp.v11i4.966. CrossRef S. Zalewski, "Design of optical systems for LED road luminaires," Applied Optics, vol. 54, no. 2, pp. 163-170, 2015, doi: 10.1364/ao.54.000163. CrossRef D. Czyzewski, "Investigation of COB LED luminance distribution," in Proceedings of 2016 IEEE Lighting Conference of the Visegrad Countries, Lumen V4 2016, 2016, pp. 1-4, CrossRef M. Jongewaard, "Guide to selecting the appropriate type of light source model," in Proc.SPIE, Aug. 2002, vol. 4775, pp. 86-98, CrossRef D. Czyzewski, "Luminance distribution of LED luminous surface," Przeglad Elektrotechniczny, vol. 86, no. 10, pp. 166-169, 2010. DirectLink D. Czyżewski, "Research on luminance distributions of chip-on-board light-emitting diodes," Crystals, vol. 9, no. 12, pp. 1-14, 2019, CrossRef J. Fang, H. Xu, W. Lv, and M. R. Luo, "59-3: Proper Luminance of HDR TV system," in SID Symposium Digest of Technical Papers, 2016, pp. 806-808, CrossRef E. A. Cooper, H. Jiang, V. Vildavski, J. E. Farrell, and A. M. Norcia, "Assessment of OLED displays for vision research.," Journal of vision, vol. 13, no. 12, pp. 1-13, 2013 CrossRef C. D. Galatanu, "Improving the Luminance Measurement from Digital Images," in 2019 International Conference on Electromechanical and Energy Systems (SIELMEN), 2019, pp. 1-4. CrossRef M. Moeck and S. Anaokar, "Illuminance analysis from high dynamic range images," LEUKOS - Journal of Illuminating Engineering Society of North America, vol. 2, no. 3, pp. 211-228, 2006, CrossRef D. Wüller and H. Gabele, "The usage of digital cameras as luminance meters," in Digital Photography III, 2007, p. 65020U CrossRef I. Fryc and E. Czech, "Spectral correction of the measurement CCD array," Optical Engineering, vol. 41, no. 10, pp. 2402-2406, 2002, CrossRef I. Fryc, "Accuracy of spectral correction of a CCD array for luminance distribution measurement," in Proc. SPIE 5064, Lightmetry 2002: Metrology and Testing Techniques Using Light, 2003, pp. 38-42 CrossRef I. Fryc, "Analysis of the spectral correction errors of illuminance meter photometric head under the influence of the diffusing element," Optical Engineering, vol. 40, no. 8, pp. 1636-1640, 2001. CrossRef S. W. Brown, G. P. Eppeldauer, and K. R. Lykke, "Facility for spectral irradiance and radiance responsivity calibrations using uniform sources," Applied Optics, vol. 45, no. 32, pp. 8218-8237, 2006 CrossRef D. W. Allen, G. P. Eppeldauer, S. W. Brown, E. A. Early, B. C. Johnson, and K. R. Lykke, "Calibration and characterization of trap detector filter radiometers," in Proc. SPIE 5151. Earth Observing Systems VIII, 2003, pp. 471-479 CrossRef I. Lewin and J. O'Farrell, "Luminaire photometry using video camera techniques," Journal of the Illuminating Engineering Society, vol. 28, no. 1, pp. 57-63, 1999, CrossRef P. Fiorentin, P. Iacomussi, and G. Raze, "Characterization and calibration of a CCD detector for light engineering," IEEE Transactions on Instrumentation and Measurement, vol. 54, no. 1, pp. 171-177, 2005 CrossRef I. Fryc and E. Czech, "Application of optical fibers and CCD array for measurement of luminance distribution," in Proc. SPIE 5064, Lightmetry 2002: Metrology and Testing Techniques Using Light, 2003, pp. 18-21, CrossRef International Organization for Standardization, "Standard ISO 14524:2009 Photography - Electronic still-picture cameras - Methods for measuring opto-electronic conversion functions (OECFs)," International Organization for Standardization Publication, 2009. CrossRef I. Fryc, "Chosen properties of a photometric detector BPYP 07," in Proc. SPIE 4517, Lightmetry: Metrology, Spectroscopy, and Testing Techniques Using Light, 2001, vol. 4517, pp. 34-36 CrossRef D. Mozyrska, I. Fryc, and M. Wyrwas, "Nonlinear numerical models of spectral power distributions of black body," PRZEGLAD ELEKTROTECHNICZNY, vol. 87, no. 4, pp. 116-119, 2011. DirectLink D. Mozyrska and I. Fryc, "Spectroradiometric data interpolation and approximation-case study," PRZEGLAD ELEKTROTECHNICZNY, vol. 85, no. 11, pp. 253-256, 2009. CrossRef